2019
DOI: 10.1111/1365-2745.13264
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition magnifies the sensitivity of desert steppe plant communities to large changes in precipitation

Abstract: Precipitation alteration and nitrogen (N) deposition caused by anthropogenic activities could profoundly affect the structure and functioning of plant communities in arid ecosystems. However, the plant community impacts conferred by large temporal changes in precipitation, especially with a concurrent increase in N deposition, remain unclear. To address this uncertainty, from 2016 to 2017, an in situ field experiment was conducted to examine the effects of five precipitation levels, two N levels and their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 80 publications
(148 reference statements)
11
62
0
1
Order By: Relevance
“…Here, we show that the shifts of CWM of plant height, SLA and LT in grassland communities with increasing precipitation are consistent between the experimental and natural gradients. This suggests that CWMs of plant height, SLA and LT are good predictor for short-or long-term responses of grass communities to precipitation changes, which is supported by the other studies in desert steppe (Ma et al, 2019). Similarly, the CWM of LCC, FDvar of LT and LCC and FDis are good predictors for short-or long-term responses of shrub communities to precipitation changes.…”
Section: Experimental Versus Natural Precipitation Gradientsupporting
confidence: 81%
“…Here, we show that the shifts of CWM of plant height, SLA and LT in grassland communities with increasing precipitation are consistent between the experimental and natural gradients. This suggests that CWMs of plant height, SLA and LT are good predictor for short-or long-term responses of grass communities to precipitation changes, which is supported by the other studies in desert steppe (Ma et al, 2019). Similarly, the CWM of LCC, FDvar of LT and LCC and FDis are good predictors for short-or long-term responses of shrub communities to precipitation changes.…”
Section: Experimental Versus Natural Precipitation Gradientsupporting
confidence: 81%
“…Moreover, anthropogenic activities have doubled nitrogen (N) inputs to terrestrial ecosystems via atmospheric deposition (Galloway et al., 2008). Various studies have now shown that these global changes can strongly threaten the temporal stability (Isbell et al., 2009; Tilman & Downing, 1994) and functioning of terrestrial ecosystems (Ma et al., 2019; Rillig et al., 2019; de Vries et al., 2012). The core components of ecosystem stability are well‐defined as resistance, that is, the ability of ecosystems to withstand perturbations, and as resilience, that is, the ability of ecosystems to return to their original state after subsequent recovery (Mariotte et al., 2013; Standish et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As water and N are the most important factors that determine the growth and survival of plant and limit the production of grassland ecosystems (Bobbink et al, ; Greaver et al, ), the altered Precip and enhanced N deposition affect grassland ecosystem functions and services that are essential for well‐being of humanity (Basto et al, ; Liu et al, ). Despite numerous reports on the effects of altered Precip and enhanced N deposition grassland ecosystems (Liu et al, ; Ma et al, ; Tian et al, ; Yang et al, ), less is known with respect to how altered Precip, enhanced N deposition, and their interaction in the alpine steppe will influence aboveground and belowground biomass allocation, especially at different soil layer (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%